The Impact of English Listening Practice Frequency on Students’ Vocabulary Skills at MAS Al-Qalam Tompong - jumratul yusuf; Sarwadi Sarwadi; Karyawan Putraidi (Universitas Qamarul Huda Badaruddin, 2025)
This study investigates the impact of English listening practice frequency on vocabulary skills among EFL learners at MAS Al-Qalam Tompong. A quasi-experimental design using a one-group pretest–posttest model was employed. Twenty-four eleventh-grade students participated in a series of activities including a pretest, four sessions of structured listening practice, a posttest, and a frequency-of-listening questionnaire. Data were analyzed using descriptive statistics, paired sample t-test, and simple linear regression. The results revealed a significant improvement in students’ vocabulary skills following regular listening practice, with the mean score increasing from 48.33 to 67.70. The paired t-test confirmed the significance of this difference (p < 0.05). Regression analysis further indicated that listening practice frequency positively influenced vocabulary mastery (? = 0.565; p = 0.004). These findings highlight the importance of incorporating systematic listening activities in EFL instruction to enhance vocabulary acquisition and strengthen learners’ overall communicative competence.